The Impact of Competency Certification Training For Occupational Health Safety Experts (K3) of Smes And Technology Startups on Companies - Sulistyowati, Dwi Andriani; Susetiyono , Agung (Publikasi Indonesia, 2023)
The aim of this study is to evaluate the impact of occupational health and safety (OHS) certification training on SMEs and technology startups. The focus is on a training program provided by the Deputy of SMEs at the Ministry of Cooperatives and SMEs to improve worker awareness, compliance, and skills in OHS. A qualitative approach was used, with data collected through in-depth interviews and observations. Respondents were employees from SMEs and technology startups who had completed OHS certification training. Descriptive analysis was used to analyze the data. The study found that OHS certification training has a positive impact on companies. The positive impacts discovered include increased worker awareness and compliance with OHS regulations, reduced risks of accidents and occupational illnesses, increased efficiency and productivity, improved quality of products and services, and reduced operating costs. However, the study also found that there are factors that influence the success or failure of OHS certification training programs, such as confidence, motivation, and support from management. Therefore, it is recommended that the Ministry of Cooperatives and SMEs continue to evaluate the training program and provide sufficient support to companies in implementing OHS training. In conclusion, OHS certification training has a positive impact on companies, particularly SMEs and technology startups. The positive impact can be enhanced by considering the factors that influence the success of the training program. Therefore, the training program needs to be continually developed and improved to increase worker awareness, compliance, and skills in OHS.